Analysis of Legal Protection for Public Shareholders in Public Limited Companies (PT Tbk) Through the Principle of Majority Rule, Minority Protection - Andria Marchelia; Muhammad Ridha Febriyani; I Gede Sandy Satria (PT. Anagata Sembagi Education, 2026)
A Public Limited Liability Company (PT Tbk), as a legal entity whose shares are widely owned by the public, presents a fundamental challenge in corporate governance: how to balance the authority of the majority with the protection of minority shareholders. The principles of majority rule and minority protection serve as the normative foundation that supports this balance within the Indonesian corporate legal framework. This study comprehensively examines how these principles are implemented in the provisions of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and relevant Financial Services Authority (OJK) regulations. The research method used is a normative juridical approach with a statutory approach and a conceptual approach. The results show that although the regulatory framework is quite comprehensive in regulating protection mechanisms, there are a number of normative gaps and practical challenges in its enforcement, particularly regarding transparency, information disclosure, and access to justice for public shareholders. This study recommends strengthening enforcement mechanisms and special regulations against oppressive actions by controlling shareholders